Knowledge and Practice of Midwives in Golestan Province, North of Iran: An Evidence-based Practice - Kouchak, Farideh; Eri, Maryam; Khojamli, Mansoor; Gorzin, Marzieh; Ghana, Samieh (Advances in Nursing & Midwifery, 2018)
Introduction: Given the role of evidence-based practice (EBP) in the improvement of patient care including midwifery care, the current study aimed at investigating knowledge and practice of midwives worked in health centers in terms of EBP in Golestan Province, North of Iran. Methods: The current cross sectional study was conducted in Golestan Province, North of Iran in 2014. Of 389 midwives worked in family health centers of Golestan Province, 262 subjects were selected using census sampling method. Data collection tool was a self-report questionnaire consisted of three parts: 1) Demographic characteristics; 2) Participants’s knowledge about EBP; 3) Participant’s practice of EBP. Data were finally analyzed with SPSS version 16. P-value < 0.05 was considered as the level of significance. Results: The mean score of the study subjects in knowledge and use of EBP were 13.2 ± 6.3 and 2.1 ± 1.2, respectively. In other words, 90% of midwives got the score < 22. Significant relationships were found between knowledge and participants’ age (P = 0.001), marital status (P = 0.008), and level of education (P = 0.039). Also, there was a significant relationship between use of EBP and type of recruitment (P = 0.014), workplace (urban or rural) (P ≥ 0.05), and age (P < 0.05). According to Spearman test, there was a remarkable, linear relationship between knowledge and use of EBP (r = 0.437). Conclusions: Knowledge and use of EBP in daily practice among midwives was poor. Given the role of EBP in the improvement of patient care, it is necessary to improve the level of knowledge and utilize EBP efficiently and effectively among healthcare workers using appropriate plans designed by health policymakers.